(untitled) (Global Journals of Research in Engineering, 2023)
In this empirical study we are proposing to conduct a longitudinal quantitative research design on a population of machines to test Hays 2022 theory that the Operating Equipment Effectiveness OpEE score with a quality status indicator will increase productivity and reduce the associated cost of maintenance CoM through improving reliability see Figure 1 In addition to this test this paper will pursue answers to the research question whether firms using status indicator s will achieve more consistent and timely maintenance than firms using standard maintenance practices as measured by the established performance indicator OpEE The expected results will show that using a quality status indicator will significantly improve maintenance timeliness and consistency which will improve overall productivity and reduce the cost of maintenance This study will provide a significant contribution to machine maintenance and productivity research by demonstrating a method to adopt quality status indicator s using sensors the Internet of Things IoT and provide proactive maintenance strategies to optimize machine productivity in a variety of use cases and industries